2005
DOI: 10.1111/j.1440-1754.2005.00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial suppuration

Abstract: Objective:  To evaluate prevalence, age, position, predisposing factors, bacteriology, clinical features and outcomes of children with subdural empyema (SDE) and brain abscess (BA). Design:  Retrospective hospital‐based study in a tertiary children's hospital. Methods:  Clinical data were reviewed on all children classified as having SDE or BA for 10.75 years from 1 January 1992 to 31 August 2003 at the Royal Alexandra Hospital for Children, Sydney, Australia. Results:  Forty‐six children with intracranial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…1,[25][26][27][28][29]31,[34][35][36][37][38][39][40][41][42][43][44][45][48][49][50][51][52][53][54][56][57][58][59][60] Many of these reports are inhomogeneous with respect to etiology, including infectious collections related to community-acquired meningitis, congenital heart disease, trauma, and previous surgery. Many reports limited to complications of sinusitis include orbital cellulitis, dural sinus thrombophlebitis, and meningitis, which were not considered in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…1,[25][26][27][28][29]31,[34][35][36][37][38][39][40][41][42][43][44][45][48][49][50][51][52][53][54][56][57][58][59][60] Many of these reports are inhomogeneous with respect to etiology, including infectious collections related to community-acquired meningitis, congenital heart disease, trauma, and previous surgery. Many reports limited to complications of sinusitis include orbital cellulitis, dural sinus thrombophlebitis, and meningitis, which were not considered in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…It is also useful for diagnosing subdural collections which are common in children ,2 years of age. 2 This diagnosis is not uncommon in our setting where the usual cause is non-typhoidal salmonella (S. M. Graham, unpublished observation) and repeated needle aspiration through the fontanelle is a part of management. Brain abscess is typically seen in older children 2,3 and so ultrasound is not helpful for diagnosis.…”
Section: Discussionmentioning
confidence: 85%
“…Recent retrospective studies from two tertiary referral hospitals in Pakistan and Australia each reported 30 cases over a 10-year period. 2,3 Most were children over 4 years of age, case fatality was 10-16% and the majority of survivors had longstanding neurological deficit. A recent review states that 25% of all brain abscesses occur in children under the age of 15 years with a peak at 4-7 years and high morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A review by Younis et al found the opposite to be the case [5]. Taken from a different perspective, Leotta et al [2] found that in all their cases of subdural empyema, this was more likely to arise secondary to acute sinusitis. This also highlights the importance of imaging of the sinuses in cases where the imaging is usually focussed upon the intracranial infection [7].…”
Section: Discussionmentioning
confidence: 95%
“…This is particularly so when acute sinusitis is the initiating illness because of common clinical features such as headache, fever, and vomiting. [2,3] The process usually rapidly progresses with variable development of meningism, focal neurology, altered conscious state, and seizures [4]. The role of neurosurgical intervention is established, but the issue of the timing and nature, if any, of surgical management of the sinuses in the acute setting remain unresolved.…”
Section: Introductionmentioning
confidence: 99%